PENGGUNAAN MEDIA SOSIAL YOUTUBE PADA MATERI PERISTIWA KERASULAN NABI MUHAMMAD SAW DALAM PEMBELAJARAN SKI DI MADRASAH IBTIDAIYAH - Syuranisa Valentini; Maria Angelita Tania Atie; Lubna Samira; Bunga Febriana Putri; Sarah Maulida; Ghaida Tsurayya; Dewi Septyaningsih; Dian Rif'iyati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The role of educational media is crucial in enhancing the effectiveness and engagement of the learning process. This study aims to examine the use of YouTube in relation to materials on the Prophethood of Muhammad SAW in the teaching of Islamic Cultural History (SKI) at the Madrasah Ibtidaiyah level, as well as the challenges involved and strategies for addressing them. The research method employed was a literature review, utilizing data sources from books, journals, and relevant studies, analyzed using descriptive qualitative methods involving data reduction, presentation, and drawing conclusions. The findings indicate that the use of YouTube is capable of increasing students’ interest, engagement, and understanding of the sequence of events. Challenges faced include facilities and infrastructure, difficulties for teachers in finding appropriate videos, technical issues, time management during the learning process, student-related factors, and other obstacles. Recommended solutions include collaboration between teachers and parents in monitoring media use, downloading educational videos and saving them to a gallery, and other measures.